Predictors of motivation for abstinence at the end of outpatient substance abuse treatment - Laudet, Alexandre B. (2010)
Commitment to abstinence, a motivational construct, is a strong predictor of reductions in drug and alcohol use. Level of commitment to abstinence at treatment end predicts sustained abstinence, a requirement for recovery. This study sought to identify predictors of commitment to abstinence at treatment end to guide clinical practice and to inform the conceptualization of motivational constructs. Polysubstance users (N = 250) recruited at the start of outpatient treatment were re-interviewed at the end of services. Based on the extant literature, potential predictors were during treatment measures of substance use and related cognitions, psychological functioning, recovery supports, stress, quality of life satisfaction, and treatment experiences. In multivariate analyses, perceived harm of future drug use, abstinence self-efficacy, quality of life satisfaction, and number of network members in 12-step recovery contributed 26.6% of the variance explained in the dependent variable, a total of 49.6% when combined with the control variables (demographics and baseline level of the outcome). Gender subgroup analyses yielded largely similar results. Clinical implications of findings for maximizing commitment to abstinence when clients leave treatment are discussed as are future research directions.